ADMINISTRATIVE STRATEGIES AND THE INTERNAL COMMUNICATION SYSTEM: LESSONS FROM THE CASE OF THE COMPANY T&L - Silva, Ismael Carlos de Oliveira; Gomes, Miriely Soares; Fonseca, Marcello Pires; de Lima, Francisco Lúcio Pinto; de Souza, Alexandre Pirangy; de Souza, Karina Medeiros Pirangy; Moçambite, Viviane da Silva Costa Novo; da Silva, Aldenor Moçambite (Seven Editora, 2024)
This scientific article presents a research with the objective of analyzing the efficiency and effectiveness of the Internal Communication System in the Company T&L. In this study, the definition of effectiveness in the communication system between the sectors of the Company was presented, as well as the level of communication and the elements that influence the sectors in their communication process. Reports on the improvement in the internal communication system, as well as its implications debated based on the view of various authors of our literature, will also be part of this one. And finally, the opinions of some will be analyzed along with the opinion of this research, concluding with the presentation of a proposal that will improve communication between all sectors of the company in order to improve respectively the other problems that are caused by the lack of good communication.DOI: https://doi.org/10.56238/sevened2024.037-084